Students’ Performance in Writing Job Application Letters in an English Correspondence Course - Novita Kusumaning Tyas; Ariana Oktavia (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
English Correspondence is an important course for university students from non-English departments as it equips them with professional writing skills needed in the workplace, including job application letter writing. This study aims to describe students’ writing outcomes in writing job application letters after receiving instruction in an English Correspondence course. The study employed a descriptive qualitative research design. The participants consisted of 22 students from a non-English department enrolled in the English Correspondence course at Stekom university. The data were obtained from students’ final job application letters and analyzed using an analytic writing assessment rubric focusing on content relevance, completeness of letter structure, organization, and use of formal English. The findings reveal that students generally achieved good writing outcomes in writing job application letters. The strongest aspect was the completeness of letter structure, indicating that most students were able to apply the standard format and components of a job application letter appropriately. Students also demonstrated relatively good performance in content relevance and use of formal English. However, weaknesses were identified in organization and language accuracy, particularly in developing coherent ideas and using grammatically accurate formal expressions. The analysis of representative excerpts from students’ letters further illustrates variations in writing quality across aspects. Overall, the findings suggest that instruction in the English Correspondence course contributed positively to students’ ability to write job application letters. This study highlights the importance of examining students’ writing outcomes holistically to provide insights for improving instructional practices in teaching professional writing.